Awareness & Achievement of Multimedia in Teacher Education - Nachimuthu, K; Vijayakumari, G. (International Journal of Asian Social Science, 2012)
Multimedia is media and content that uses a combination of different media content forms. Multimedia term was coined by Bob Goldstein in July 1966. This research study aimed at to know the awareness of Multimedia programme for teacher education; and to apply the Multimedia programme for the teacher education at Master of Education (M.Ed) level and to find out their achievement level. This experimental method was adopted the convenience sampling of 50 Master of Education trainees with biology background in ten different colleges of education in Namakkal and Salem District of Tamilnadu State of Indian Country. They have to shown the prepared “Genetics” multimedia contents and also noted their achievement along with filled the Multimedia awareness questionnaire. The investigators found out that, there is a significant difference in their awareness („t‟-7.17) in relation to Gender as well as in their achievement („t‟-5.38). They concluded that a multimedia content can have a strong effect on their mind and senses. This paper also gives importance of multimedia in education and its types as well as recommendations.